Assessment of Cardiometabolic Health, Diet and Physical Activity in Helicopter Rescue Paramedics. (4th May 2022) - Meadley, Ben; Perraton, Luke; Smith, Karen; Bonham, Maxine P.; Bowles, Kelly-Ann
Abstract: Objective: Shift work is an established risk factor for weight gain, cardiovascular disease, Type II diabetes mellitus, and impaired health-related quality of life (HRQoL). Prolonged exposure to shift work is common in paramedics and other emergency medical service (EMS) providers. Sub-populations of EMS workers may have varying health outcomes when exposed to shift work, but the reasons for this have not been investigated. We sought to describe cardiometabolic health, dietary patterns, physical activity, and health-related quality of life (HRQoL) in a sample of experienced intensive care flight paramedics (ICFPs) working for a Helicopter Emergency Medical Service (HEMS). Methods: Fifteen paramedics (median age 45, IQR 42–48 years) were recruited to undertake a range of health assessments. These included a food frequency questionnaire to assess dietary patterns, sampling of biomarkers to determine cardiometabolic health risk, maximal aerobic capacity assessment via treadmill running and assessment of HRQoL via the SF-36 survey. In an extension of the study protocol, ten of the fifteen participants wore a physical activity monitor for one year. Results: Median (IQR) weight was 79.9 (72.3–89.3) kg, body fat percentage 23.3 (21.9–26.5) %, body mass index (BMI) 25.1 (21.9–27.4) kg.m 2, and waist to height ratio 0.48 (0.45–0.54). Dietary analyses showed high discretionary food intake. Biomarkers of cardiometabolic health risk were all within normal range. HRQoL was 86.2/100 for physical health and 85.1/100 for mental health. V̇O2max was 47.0 (43.0–54.6) mL.kg −1 .min −1 . The ten participants that wore activity monitors completed 11, 235 (8334–15, 380) steps per day and undertook 50 (12–98) minutes per day/350 (84–686) minutes per week of moderate to vigorous physical activity. The least amount of physical activity was conducted on day shifts. Conclusions: For ICFPs included in this study, HRQoL, cardiometabolic and physical activity outcomes are representative of good health. Although shift work influences the amount of physical activity, ICFPs exceeded minimum recommendations even when rostered to duty. Despite lengthy careers in EMS, ICFPs demonstrate an excellent health profile that is likely due to high physical activity levels and healthy BMI. This information may be useful in guiding health interventions in the wider EMS workforce.